2022
DOI: 10.3390/ma15051922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sorption Materials from Low Grade Titanium Raw Materials

Abstract: In this paper, a universal technology is proposed for processing low-titanium mineral raw material—apatite-nepheline ore waste, including its treatment with sulfuric or hydrochloric acid in a two-stage mode with a sequential increase in the concentration. This technique allowed us to remove nepheline and apatite in the first stage and achieve a titanium mineral content of TiO2 of more than 30%; in the second stage, we were able to convert the titanium into its precursors—titanyl sulfate monohydrate TiOSO4·H2O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…При получении композиционного сорбента (КТФ) изучено влияние состава и структуры ТСО (рис. 3) на механизм кристаллизации твердой фазы при взаимодействии его с фосфорной кислотой [2]. Установлено, что в гетерогенной системе TiO2-SiO2-H3PO4-H2O с ростом СH3PO4 и температуры синтеза степень химического преобразования ТСО незначительна.…”
Section: результатыunclassified
“…При получении композиционного сорбента (КТФ) изучено влияние состава и структуры ТСО (рис. 3) на механизм кристаллизации твердой фазы при взаимодействии его с фосфорной кислотой [2]. Установлено, что в гетерогенной системе TiO2-SiO2-H3PO4-H2O с ростом СH3PO4 и температуры синтеза степень химического преобразования ТСО незначительна.…”
Section: результатыunclassified
“…It is known that from the current [14,15] and stored wastes of processing apatite-nepheline ores [16], it is possible to recover titanite concentrate with 28-34 % TiO2 content applying the flotation-magnetic technology. Studies have shown that such titanite concentrate can be used to produce sorbents [17,18], tanning agents and sealants [19,20], composite electrode materials [21], and other inorganic materials that are in demand on the Russian market [22]. Titanite content in apatite-nepheline ores of the Khibiny deposits is generally low, amounting to 3-5 %.…”
mentioning
confidence: 99%